Respuesta :

hehha
-6 = 1.8 hope this helps

There is no solution of the given expression.

Given expression is:

→ [tex]3(0.5x -4) = \frac{3}{2x} -1.2[/tex]

By solving the bracket, we get

→ [tex]1.5x -12 = \frac{3}{2x} -1.2[/tex]

By adding "12" both sides, we get

→ [tex]1.5x -12 +12= \frac{3}{2x} -1.2+12[/tex]

→                 [tex]1.5x = \frac{3}{2x} +10.8[/tex]

By combining the like terms, we get

→                     [tex]0 = 10.8[/tex]

Thus the response above is right.

Learn more about equation here:

https://brainly.com/question/20992770

ACCESS MORE